Transforming Education Summit: National Consultations Report for Saint Lucia - Edward, Marcus (Ministry of Education, St. Lucia, 2022)
Linked to the proposed formulation of the new Education Sector Plan is the review of national education targets and benchmarks to engender recommitment to local, regional and international education goals. In many areas St. Lucia was on track towards meeting the SDG targets by the 2030 deadline. While the COVID-19 pandemic has significantly retarded progress as much needed 4 resources were diverted to pressing national issues, the Ministry of Education remains resolute in its pursuit of the SDG targets as key pillars for physical, social and economic development of the island nation. The national consultations provided opportunities to share with stakeholders the many commitments of the education sector to the regional and international community. The Ministry has made it clear to stakeholders its commitment towards the local realization of the SDG targets.
Keywords: transforming education